1979
DOI: 10.1056/nejm197903013000903
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cushing's Disease by o,p′DDD

Abstract: In a study of nonsurgical therapy of Cushing's disease, 62 patients received O,p'-dichlorodiphenyldichloroethane (O,p'DDD), 16 of whom also received cobalt irradiation of the pituitary. After an initial treatment period averaging eight months, a remission of the disease was obtained in 38 of the 46 patients given O,p'DDD alone and in all patients who received drug combined with radiation. Although 60 per cent of these patients subsequently relapsed, additional courses of drug or radiation therapy were usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
2

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(97 citation statements)
references
References 16 publications
2
93
0
2
Order By: Relevance
“…There is now evidence for the anti-proliferative and anti-secretory effects of mitotane in adrenocortical cancer (18,19,20), but there are no recent data on its long-term efficacy or safety in the treatment of CD. The largest study to date was published from our center in 1979 and included 62 patients treated with mitotane, of whom 24 also received pituitary irradiation (21). The aim of the current study was to analyze the efficacy and side effects of mitotane as a first-or second-line treatment in patients with CD in a single center.…”
Section: Introductionmentioning
confidence: 99%
“…There is now evidence for the anti-proliferative and anti-secretory effects of mitotane in adrenocortical cancer (18,19,20), but there are no recent data on its long-term efficacy or safety in the treatment of CD. The largest study to date was published from our center in 1979 and included 62 patients treated with mitotane, of whom 24 also received pituitary irradiation (21). The aim of the current study was to analyze the efficacy and side effects of mitotane as a first-or second-line treatment in patients with CD in a single center.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to inhibit cortisol production via inhibition of multiple steroidogenic enzymes and to be efficacious in the treatment of CD (Young et al 1973, Luton et al 1979. Mitotane has a slow onset of action and based on its lipophilic nature, it is stored in adipose tissue, ensuring a long half-life of 18-159 days (Nieman 2002).…”
Section: Inhibitors Of Adrenocortical Steroidogenesismentioning
confidence: 99%
“…up to 16 weeks, whereas long-term treatment resulted in biochemical remission in about 80% of patients, although these patients were also treated with radiotherapy (Verhelst et al 1991). Mitotane, at lower dosages, can be useful in the treatment of CD (Luton et al 1979, Schteingart et al 1980, Kamenicky et al 2011. Schteingart et al (1980) reported clinical and biochemical remission of CD in 80% of patients treated with mitotane and pituitary irradiation.…”
Section: R Van Der Pas Et Al: Developments In the Medical Treatment mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the onset of its action is slow (weeks or months), and the adverse effects associated with mitotane therapy (mainly digestive and neurological) require careful monitoring of drug levels. This kind of therapy is routinely used in only a few centers (33), and is more useful for adrenocarcinoma treatment.…”
Section: Treatment and Managementmentioning
confidence: 99%